Efect of lnf (cna - cnb) enzyme complex in the drying process and the coffee quality - Franco Júnior, Kleso Silva; Santos, Douglas Freitas; Silva, Carlos Henrique da; Silva Neto, José Francisco; Brigante, Giselle Prado; Paiva, Leandro Carlos (Coffee Science - ISSN 1984-3909, 2020)
The world demand for quality coffee is growing and the market is increasingly demanding for sustainable practices, leading coffee growers to search for new coffee processing processes always aiming for maximum quality. The objective of this work was to verify the benefits of using the LNF CNA - CNB enzyme complex in the postharvest process, in order to compare the results of drying time and the final beverage quality of the product. The research was carried out at Fazenda Iracema, municipality of Machado - Minas Gerais, with mechanically harvested coffees from the cultivar Mundo Novo, with 80% maturation, and the treatments were: natural and washed coffee, with and without application of enzymatic complex and drying in suspended, concrete and mixed courtyards (initially in the yard and finished in rotary dryers), the enzyme complex dosage was 1 ml CNB + 2.5 ml CNA per liter of water, applied to 60 liters of coffee. The experimental design was in randomized blocks, in a 2 x 2 x 3 factorial scheme (2- types of “washed or natural” processing; 2- with and without enzymatic application; 3 - “suspended, concrete and drying” drying forms), with 4 repetitions per treatment, totaling 48 experimental plots. The coffees were dried to 11.5% humidity and evaluated by the SCAA. It was concluded that the use of LNF (CNA - CNB) enzymatic complex in the coffee drying process did not influence the final drying time results, nor did it influence the coffee beverage aroma attributes. The drying forms directly influence the drying time. Enzymes; post-harvest; specialty coffees.